Effect of postremission high dose cytarabine-based consolidation chemotherapy before allogenic stem cell transplantation in outcomes of acute myeloid leukemia patients. Issue 6 (December 2018) - Ciftciler, Rafiye; Demiroglu, Haluk; Buyukasık, Yahya; Okay, Mufide; Aksu, Salih; Sayınalp, Nilgun; Malkan, Umit Yavuz; Haznedaroglu, Ibrahim Celalettin; Ozcebe, Osman; Goker, Hakan
Abstract: Background and Aim: This is a retrospective study aiming to investigate the effect of the number of high dose cytarabine-based chemotherapy (HiDAC) courses in patients with acute myeloid leukemia before allogenic stem cell transplantation (ASCT). Materials and Methods: A total of 110 patients with acute myeloid leukemia who received ASCT between 2001 and 2018 were included in the study. Results: Of the 110 patients, 25 (23%) patients received one course of HiDAC, 42 (38%) patients received two courses of HiDAC, 34 (31%) patients received three courses of HiDAC and 9 (8%) patients received four courses of HiDAC. Median follow-up for survivors was 71 months (range 4–186) for all patients. The 3-year overall survival for patients who received one course of HiDAC and patients who received more than one course of HiDAC were 49% and 70%, respectively (p = 0.29). The 3-year disease free survival (DFS) for patients who received one course of HiDAC and patients who received more than one course of HiDAC were 38% and 66%, respectively (p = 0.05). There was no statistically significant difference in OS between patients who received one or more than one consolidation chemotherapy. But there was nearly a statistically significant difference between patients who received one or more than one consolidation chemotherapy in DFS. Conclusion: In conclusion, the administration of more than one consolidation chemotherapy may provide longer DFS, however the number of consolidation chemotherapy is not associated with statistically significant differences in overall outcomes.